THE ARBITRATION AWARD AND ITS EFFECTIVENESS-A COMPARATIVE STUDY BETWEEN THE IRAQI ARBITRATION LAW AND THE NEW LIBYAN ARBITRATION LAW NO. 10 OF 2023 - Mustafa Sebahi Kazem Sikkban Al-Aboudi (Scholar Express Journals, 2025)
Arbitration means that the subject of the dispute is related to international trade, and in terms of international arbitration being a means of resolving a dispute between two or more persons of international law by a ruling issued by an arbitrator or a group of arbitrators chosen by the disputing countries, and with the aim of identifying the importance of having a special law on arbitration to resolve disputes in the international trade fair, especially after external openness and attracting foreign investments, and to achieve this, it is necessary to research comparative laws, especially Libyan Arbitration Law No. 10 of 2023 in order to reach a result that confirms the necessity of enacting a special law on arbitration in Iraq, and in this study, national legal texts were analyzed and comparative laws and international agreements were studied, relying on the descriptive analytical approach, as well as the comparative approach, and at the end of the research, a conclusion was drawn up that includes the most important results reached by the research, in light of which a set of recommendations were proposed, we mention from the results of the research: The arbitration agreement includes the characteristics of contracts, whether civil or commercial, and they are named contracts included in a special law, and stipulate the condition of writing as a basic legal condition, otherwise it is considered void, and it can be applied Arbitration on fixed-term contracts under the agreement concluded between the parties.
Keywords: decision; arbitration; effectiveness